Autonomic dysfunction in older individuals: The contributions of multiple brain diseases and diabetes. Issue 4 (24th May 2022) - Sakakibara, Ryuji; Sawai, Setsu; Ogata, Tsuyoshi; Iimura, Ayako
Abstract: The present article reviewed autonomic dysfunction in older individuals. The following estimated incidences are reported among octogenarians (age >80 years): white matter disease (WMD), 80%; Alzheimer's disease (AD), 33%; and dementia with Lewy bodies (DLB), 7%–8%. A combination of AD + WMD is the most common. The estimated incidence in octogenarians of diabetes that produces small fiber neuropathy is 30%. Orthostatic hypotension, overactive bladder, and bowel motility dysfunction also increase with age. The links between all of these disorders are still obscure, but associations have been postulated between orthostatic hypotension with DLB and diabetes, between overactive bladder with WMD and DLB (AD in part), and between bowel motility dysfunction with DLB and diabetes. Management and care of autonomic dysfunction is thus necessary to maximize the quality of life of older individuals and avoid emergency of syncope, urinary retention, or ileus.